Salmonella sp Contamination on Chicken Eggs and Duck Eggs at the Antasari Traditional Market, Banjarmasin, Indonesia - Sa'adah, Sa'adah; Dwiyanti, Ratih Dewi; Lutpiatina, Leka (Tropical Health and Medical Research, 2024)
Chicken eggs and duck eggs can be a source of transmission of Salmonellosis. Salmonella bacteria can penetrate the eggshell, or the egg's contents can become directly contaminated with Salmonella in the reproductive organs before the shell covers the egg. This research aims to analyze Salmonella sp in chicken and duck eggs at the Antasari Traditional Market in Banjarmasin, Indonesia. Samples were taken by purposive sampling with the criteria for cracked/broken eggs and intact eggs: 3 chicken eggs and three duck eggs from 6 traders so that the total sample was 24. For the identification of bacteria, microscopic tests and biochemical tests were used on the identification media. The results showed Salmonella sp in duck eggs and no Salmonella in chicken eggs. In all samples of chicken and duck eggs, 12.50% of Salmonella sp, 37.50% of Klebsiella sp, 12.50% of Proteus sp, and 37.50% of Pseudomonas sp were found. Suggestions for consumers are to pay more attention to the hygiene and sanitation of traders before buying eggs, choose clean eggs, store eggs in the refrigerator, and cook eggs until they are cooked.